Analisis Efektivitas dan Kontribusi Laba BUMD Terhadap Pendapatan Asli Daerah (PAD) Kota Bandung - Astrie Merisa Ramadanti; Rahma Nazila Muhammad; Aisyah Vanadia Rubianto (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This research aims to understand the effectiveness and contribution of BUMD profits to Bandung PAD, as well as the obstacles faced and the efforts made to increase profits. The type of research used is a mixed method. The population of this study is BUMD in Bandung City, and the sampling technique used is a saturated sample. The data types used are the literature data and the subject data. The data sources used are second-hand data and original data. The data analysis techniques in this study include effectiveness analysis and contribution analysis. The results of data analysis show that the effectiveness of the profit of the Bandung City BUMD is still in the ineffective category, with a very minimal contribution. There are obstacles faced by Bandung City BUMD in increasing profits, namely company management, business capital capabilities, asset maintenance, service capabilities, tariffs, and human resources. Efforts are being made by BUMD Bandung City to overcome this and to increase profits, namely by reducing operational costs, developing the use of information technology, maintaining and utilizing assets optimally, providing convenience in service, increasing employee competence.